Calling, Conflict and Consecration: The Testament of Ida Scudder of Vellore - Reena Mary George (Health for All Nations, 2014)
How does the hand of God grasp a hesitant human hand to reach out to a world that needs health and wholeness?This article describes how one night, a young Ida Scudder experienced a painful and life changing encounter with God. Through her first person account and her personal parable, it traces the conflict, surrender, fruitfulness and breaking points that followed - on a journey that led from a one-room dispensary to the Christian Medical College, Vellore. For those who feel prompted to serve in health care, it is a testimony of the power of a vocational call, and the provision of God in the face of human inadequacy.